Microbial carbon and nitrogen cycling responses to drought and temperature in differently managed mountain grasslands. (August 2019) - Fuchslueger, Lucia; Wild, Birgit; Mooshammer, Maria; Takriti, Mounir; Kienzl, Sandra; Knoltsch, Anna; Hofhansl, Florian; Bahn, Michael; Richter, Andreas
Abstract: Grassland management can modify soil microbial carbon (C) and nitrogen (N) cycling, affecting the resistance to extreme weather events, which are predicted to increase in frequency and magnitude in the near future. However, effects of grassland management on microbial C and N cycling and their responses to extreme weather events, such as droughts and heatwaves, have rarely been tested in a combined approach. We therefore investigated whether grassland management affects microbial C and N cycling responses to drought and temperature manipulation. We collected soils from in situ drought experiments conducted in an extensively managed and an abandoned mountain grassland and incubated them at two temperature levels. We measured microbial respiration and substrate incorporation, as well as gross rates of organic and inorganic N cycling to estimate microbial C and N use efficiencies (CUE and NUE). The managed grassland was characterized by lower microbial biomass, lower fungi to bacteria ratio, and higher microbial CUE, but only slightly different microbial NUE. At both sites drought induced a shift in microbial community composition driven by an increase in Gram-positive bacterial abundance. Drought significantly reduced C substrate respiration and incorporation by microbes at both sites, while microbial CUE remained constant. In contrast, drought increased gross rates of N mineralization at both sites, whereas gross amino acid uptake rates only marginally changed. We observed a significant direct, as well as interactive effect between land management and drought on microbial NUE. Increased temperatures significantly stimulated microbial respiration and reduced microbial CUE independent of drought or land management. Although microbial N processing rates showed no clear response, microbial NUE significantly decreased at higher temperatures. In summary in our study, microbial CUE, in particular respiration, is more responsive to temperature changes. Although N processing rates were stronger responding to drought than to temperature microbial NUE was affected by both drought and temperature increase. We conclude that direct effects of drought and heatwaves can induce different responses in soil microbial C and N cycling similarly in the studied land management systems. Highlights: Microbial CUE, but not NUE, was higher in managed compared to abandoned grasslands. Drought reduced microbial C metabolism at constant CUE. Drought increased gross N mineralization, but affected NUE interactively with land management. Higher temperatures reduced CUE and NUE. Only minimal interactive effects of drought and temperature were observed.